Validation of the Czech Montreal Cognitive Assessment for Mild Cognitive Impairment due to Alzheimer Disease and Czech Norms in 1,552 Elderly Persons - Bartos, Ales; Fayette, Dan (Dementia and geriatric cognitive disorders, 2018)
BACKGROUND: The Czech version of the Montreal Cognitive Assessment (MoCA-CZ) and delayed recall of 5 words have not been validated in patients with mild cognitive impairment (MCI) due to Alzheimer disease (AD) and compared to norms of a large population. METHOD: The MoCA-CZ was administered to 1,600 elderly individuals in 2 groups consisting of 48 patients with MCI due to AD (AD-MCI) and 1,552 normal elderly adults. RESULTS: MoCA-CZ scores were significantly lower in the AD-MCI patients than in the normal elderly (21 ± 4 vs. 26 ± 3 points; p = 0.03). Under the recommended cutoff score of ≤25, the MoCA-CZ demonstrated an excellent sensitivity of 94% but a low specificity of 62%. When the score was reduced to ≤24, the MoCA-CZ showed an optimal sensitivity of 87% for AD-MCI and a specificity of 72%. Normal elderly persons should recall at least 2 words after delay (sensitivity 80%, specificity 74%). Several cutoff points were derived from normative data stratified by age and education. CONCLUSIONS: The cutoff for AD-MCI and stratified norms are available for the MoCA total score and delayed recall of the Czech version. The cut-off scores of the MoCA-CZ, sensitivity, and specificity are lower than in the original study.
Keywords: testy pro posouzení mentálních funkcí a demence; Cognitive Dysfunction; rozpomínání; lidé; Mental Recall; Cutoff; Validation; Mild cognitive impairment; Norm; senzitivita a specificita; neuropsychologické testy; Female; Dementia; Sensitivity and Specificity; Alzheimerova nemoc; Alzheimer disease; Screening; Montreal Cognitive Assessment; Humans; Neuropsychological Tests; Self Concept; Česká republika; překládání; mužské pohlaví; Alzheimer Disease; sebepojetí; Mental Status and Dementia Tests; Czech Republic; ženské pohlaví; Aged, 80 and over; senioři nad 80 let; Male; Aged; Reproducibility of Results; reprodukovatelnost výsledků; Translating; kognitivní dysfunkce; senioři